2001
DOI: 10.1159/000046217
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Related Determinants of Inflammation in Patients on Peritoneal Dialysis

Abstract: Aims: We studied markers of monocyte activation, i.e., the cell surface expression of CD11b and CD62L, and the serum concentrations of monocyte chemotactic protein 1 (MCP-1; a monocyte-specific chemoattractant) and soluble vascular cell adhesion molecule 1 (sVCAM-1; an adhesion molecule involved in monocyte recruitment) in 20 patients on peritoneal dialysis (PD), in 25 patients with chronic renal insufficiency, and in 27 healthy subjects. Results: Monocytes obtained from the peripheral blood of PD patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The plasma concentration of MCP-1 was increased significantly in PD and HD patients, and the plasma concentration of soluble TGF-␤ was increased in HD patients only, confirming previous reports (33)(34)(35)(36). MCP-1 is associated with macrophage infiltration into the peritoneal cavity of PD patients and correlates with soluble adhesion molecule expression in HD (33,37).…”
Section: Discussionsupporting
confidence: 89%
“…The plasma concentration of MCP-1 was increased significantly in PD and HD patients, and the plasma concentration of soluble TGF-␤ was increased in HD patients only, confirming previous reports (33)(34)(35)(36). MCP-1 is associated with macrophage infiltration into the peritoneal cavity of PD patients and correlates with soluble adhesion molecule expression in HD (33,37).…”
Section: Discussionsupporting
confidence: 89%
“…As reported earlier [20,21], the concentration of sVCAM-1 was significantly higher in patients with kidney diseases as compared to healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
“…Informed consent was obtained and the study was approved by the Ethics Committee of the Karolinska Hospital. Most of the patients participating in this study have been described in two recent studies [20,21].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies demonstrated that activated monocytes increased cell surface expression of CD62L (L-selectin) prior to their migration into injured tissues (11,25). Therefore, we used flow cytometry to examine CD62L expression on monocytes during liver injury (Fig.…”
Section: Foxm1 Deficiency Does Not Influence Monocyte Proliferation Bmentioning
confidence: 99%